Consumer Perception of Electric Cars in Hungary – Theoretical Considerations and Empirical Results - Németh, Tamás; Kovács, László (International Journal of Engineering and Management Sciences, 2022)
Electric cars are becoming increasingly popular in the automotive industry and among consumers; partly as a result of their environmentally friendly characteristics. The aim of the study is to compare the main characteristics of electric and conventional cars in the context of environmental protection. In the first half of the study, we present the life cycle of electric and conventional cars and we compare the overall environmental impact traditional an electric vehicles. We point out that although the operation of an electric car does not pollute the environment locally, the manufacture, charging and disposal of batteries required for operation raises several issues related to environmental pollution. In the second part, we examine the respondents' attitudes towards electric cars based on our own questionnaire research. On the basis of the answers, it can be said that consumers still consider electric cars expensive and are aware that electric cars address some pollution issues to a small extent.